Intubação traqueal - Matsumoto, Toshio (2007)
OBJECTIVE: To review current concepts related to the procedure of tracheal intubation in children. SOURCES: Relevant articles published from 1968 to 2006 were selected from the MEDLINE, LILACS and SciELO databases, using the keywords intubation, tracheal intubation, child, rapid sequence intubation and pediatric airway. SUMMARY OF THE FINDINGS: Airway management in children is related to their physiology and anatomy, in addition to specific factors (inherent pathological conditions, such as malformations or acquired conditions) which have a decisive influence on success. Principal indications are in order to maintain the airway patent and to control ventilation. Laryngoscopy and tracheal intubation cause cardiovascular alterations and affect airway reactivity. The use of tubes with cuffs is not prohibited, as long as the correct size for the child is chosen. A difficult airway can be identified against the Mallampati scale and by direct laryngoscopy. Rapid sequence intubation is being recommended more and more often in pediatrics, since it facilitates the procedure and presents fewer complications. Tracheal intubation should be carried out in an adequate manner in special circumstances (eaten recently, neurological dysfunction, unstable spinal column, upper airway obstruction, laryngotracheal injuries, injuries to the eyeball). Extubation should be meticulously planned, since there is chance of failure and a need for reintubation. CONCLUSIONS: Tracheal intubation of children requires knowledge, skill and experience, since, if the procedure is carried out by inexperienced pediatricians, it can result in life-threatening complications.